Lingaka Aaadharma Nepali ra Bhojpuri Bhashako Wakyagathanko Byatireki Bishleshan - Sharma, Bishwambher Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
Abstract in Nepali is available on Pdf. Academic Voices Vol.6 2016: 69-73